Critical perspectives in politics and socio-economic development in Ghana - Tettey, W. J. (African social studies series ;, 2003)
This volume provides a comprehensive and integrated analysis of Ghanaian politics, economy and society, outlining tensions, dilemmas and prospects with which the country has to contend.